Cyclopentenone Prostaglandins: Biologically Active Lipid Mediators Targeting Inflammation - Lee, Bohae Rachel; Paing, May Hnin; Sharma-Walia, Neelam (Frontiers in Physiology, 2021)
Cyclopentenone prostaglandins (cyPGs) are biologically active lipid mediators, including PGA2, PGA1, PGJ2, and its metabolites. cyPGs are essential regulators of inflammation, cell proliferation, apoptosis, angiogenesis, cell migration, and stem cell activity. cyPGs biologically act on multiple cellular targets, including transcription factors and signal transduction pathways. cyPGs regulate the inflammatory response by interfering with NF-κB, AP-1, MAPK, and JAK/STAT signaling pathways via both a group of nuclear receptor peroxisome proliferator-activated receptor-gamma (PPAR-γ) dependent and PPAR-γ independent mechanisms. cyPGs promote the resolution of chronic inflammation associated with cancers and pathogen (bacterial, viral, and parasitic) infection. cyPGs exhibit potent effects on viral infections by repressing viral protein synthesis, altering viral protein glycosylation, inhibiting virus transmission, and reducing virus-induced inflammation. We summarize their anti-proliferative, pro-apoptotic, cytoprotective, antioxidant, anti-angiogenic, anti-inflammatory, pro-resolution, and anti-metastatic potential. These properties render them unique therapeutic value, especially in resolving inflammation and could be used in adjunct with other existing therapies. We also discuss other α, β -unsaturated carbonyl lipids and cyPGs like isoprostanes (IsoPs) compounds.